2018
DOI: 10.24289/ijsser.400018
|View full text |Cite
|
Sign up to set email alerts
|

Temel Eğitim Bölümü öğretmen adayları ve eğitim programı: Bir metafor çalışması

Abstract: ÖzBu araştırmanın amacı, Temel Eğitim Bölümü öğrencilerinin eğitim programı kavramı ile ilgili görüşlerinin metaforlar yolu ile incelenmesidir. Araştırmanın çalışma grubunu 2016 -2017 eğitim-öğretim yılı bahar döneminde Abant İzzet Baysal Üniversitesi Eğitim Fakültesi Temel Eğitim Bölümünde öğrenim gören son sınıf öğrencileri (n=83) oluşturmaktadır. Araştırmada olgubilim deseni kullanılmış ve öğretmen adaylarından "Eğitim prog-ramı………… benzer; çünkü ………" cümlesini tamamlamaları istenmiştir. Verilerin analizind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Because one of the most important features of the curriculum is to guide practitioners. Akınoğlu (2017), Fırat Durdukoca (2017), and Yıldız, Özen, and Yıldız (2018 concluded that teacher candidates perceive the curriculum as a guide for teachers while teaching. The findings of a study by Oyetoro and Kareem (2022) and Yurdakul (2015) indicate that preservice teachers perceive the curriculum as a guide to teachers.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Because one of the most important features of the curriculum is to guide practitioners. Akınoğlu (2017), Fırat Durdukoca (2017), and Yıldız, Özen, and Yıldız (2018 concluded that teacher candidates perceive the curriculum as a guide for teachers while teaching. The findings of a study by Oyetoro and Kareem (2022) and Yurdakul (2015) indicate that preservice teachers perceive the curriculum as a guide to teachers.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Öğretmenler ve öğretmen adaylarının eğitim programına ilişkin algılarını ifade ettikleri metaforların branşlar açısından dağılımlarına bakıldığında, sınıf öğretmenliği branşındaki öğretmenler ve adaylar genel olarak programın dış görünümü iyi ama içi boş nesne olarak görmektedirler. Yıldız, Özen, Yıldız (2018) araştırmalarında öğretmen adaylarının, eğitim programı kavramını hem olumlu hem de olumsuz metaforlarla açıkladıkları, eğitim programı kavramını genellikle cansız varlıklarla (çocuk, ağaç, çiçek vb. hariç) ilişkilendirerek ifade ettikleri görülmüş ve öğretmen adaylarının eğitim programı kavramına ilişkin algılarının olumlu ve olumsuz olduğu belirlenmiştir.…”
Section: Sonuç Tartişma Ve öNeri̇lerunclassified
“…In this context, metaphors constitute a bridge between the past and the present, theory and practice in the learning-teaching process. It is possible to use metaphors to increase students' motivation in order to reach correct answers for the solution of certain problems, to help teachers and students to define, understand, perceive and focus the learning-teaching environment (Yıldız et al, 2018). On the other hand, metaphors help to reveal how a concept or phenomenon is perceived (Aydın, 2011).…”
Section: Introductionmentioning
confidence: 99%